The Curious Culture of Economic Theory - Ran Spiegler (The MIT Press, 2024)
An essay collection that insightfully explores the professional culture of contemporary economic theory, highlighting key features of successful economic theory from the last quarter century.When is a theoretical result taken seriously enough for economic application? How do theorists actively try to influence this judgment? What determines whether a new theoretical subfield adopts a "pure" or an "applied" style? How do theorists respond to economists' penchant for "rational" explanations of human behavior? These are just some of the questions regarding the professional culture of contemporary economic theory that Ran Spiegler attempts to answer in this incisive essay collection, The Curious Culture of Economic Theory. In exploring these questions, Spiegler addresses the norms that economic theorists apply as they produce, evaluate, and disseminate research. Introducing a new genre—a kind of cultural criticism of economic theory—the essays in this unique collection highlight elements of style and rhetoric that characterize classic pieces of economic theory from the last quarter century. For each piece, Spiegler offers a precise yet accessible exposition of modern classics of economic theory while placing them in the broader context of the field's professional culture. Affectionate in its criticism and anthropological in its approach, The Curious Culture of Economic Theory is as valuable a complement to standard textbooks in graduate-level economic theory, game theory, and behavioral economics as it is to the libraries of practicing economic theorists, academic economists, historians of economic thought, and philosophers of economics.
Keywords: 330; Economic theory; modern economic thought; game theory; rhetoric of economics; style of economics; culture of economics; behavioral economics